STUDY OF NON-STANDARD ISSUES IN GENERAL SECONDARY EDUCATION AND ACADEMIC LYCEUMS (Web of Teachers: Inderscience Research, 2025)
This article highlights the importance, methodology and practical approaches of studying non-standard issues in general secondary schools and academic lyceums. Non-standard problems are complex problems that cannot be solved by traditional methods and require creative and critical thinking. These problems are a convenient tool for developing students' mathematical logic, forming analytical thinking skills, and teaching a creative approach to real-life problems. The article analyzes the types of non-standard problems, methods of solving them, the effectiveness of their use in the educational process, as well as the role of the environment created for teachers and students. It is emphasized that studying the solution of these problems in academic lyceums serves to deepen scientific and practical knowledge. According to the results of the research, the inclusion of non-standard issues in the curriculum helps to significantly increase students' independent thinking, innovative approach and creativity. This article is aimed at revealing the didactic possibilities of non-standard issues for teachers, methodologists and other specialists involved in the educational process.